If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m = -2 + 3m Solving 5m = -2 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 5m + -3m = -2 + 3m + -3m Combine like terms: 5m + -3m = 2m 2m = -2 + 3m + -3m Combine like terms: 3m + -3m = 0 2m = -2 + 0 2m = -2 Divide each side by '2'. m = -1 Simplifying m = -1
| m/6-1.5=-7 | | 6x+20=38 | | 4t-5tu= | | 4x-6=-16-7 | | 4-3x=-1x+4-2x | | r-1.3=1.1 | | 7x+3(x+4)=-18 | | 5x-4=-2+3x | | 158-2x=34x+22 | | x^2-14x+29=-3x+5 | | 8m^2-16m+8=0 | | 12-7x=177-42x | | x^2-18x+40=-5x | | 3x+36=5x*12 | | 7a+3=2a+8 | | 7x-6=70 | | x-x/10=189 | | 3y^3+2y^2-9y-6= | | k-3.5=21 | | 4x+3x-7=0 | | 71-12.50=c | | -62-7x=177-42x | | 4x^3-256= | | 5x+12=-2(6x+11) | | 3(x+3)=27 | | x-19=-33 | | x+29=4 | | 9+9=90 | | x+22=11 | | m^2+m-30=0 | | 3x+40=6x+14 | | 10x-9=-8x+3 |